2007
DOI: 10.1071/wr07043
|View full text |Cite
|
Sign up to set email alerts
|

Using population genetic tools to develop a control strategy for feral cats (Felis catus) in Hawai'i

Abstract: Abstract. Population genetics can provide information about the demographics and dynamics of invasive species that is beneficial for developing effective control strategies. We studied the population genetics of feral cats on Hawai'i Island by microsatellite analysis to evaluate genetic diversity and population structure, assess gene flow and connectivity among three populations, identify potential source populations, characterise population dynamics, and evaluate sex-biased dispersal. High genetic diversity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 60 publications
3
20
0
1
Order By: Relevance
“…Currently, studies utilizing genetic information have focused on island situations (Rollins et al . 2006; Hansen et al . 2007) where limited post‐colonization gene flow between islands results in detectable population structure clearly identifying eradication units.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, studies utilizing genetic information have focused on island situations (Rollins et al . 2006; Hansen et al . 2007) where limited post‐colonization gene flow between islands results in detectable population structure clearly identifying eradication units.…”
Section: Resultsmentioning
confidence: 99%
“…Ongoing development of biological controls (Hoddle 2004), and habitat manipulation (Buckley 2008) may improve the efficiency of current control methods, and enable a broader range of invasive species to be managed. Furthermore, development and adoption of new technologies such as fertility control treatments for feral vertebrates (Jewgenow et al 2006) or use of population genetics for planning control strategies (Hansen et al 2007) may substantially improve our ability to ameliorate the impacts of invasive species.…”
Section: Managing Established Invasive Alien Speciesmentioning
confidence: 99%
“…Van Aarde (1983) found that feral cat sex ratios are near 1 : 1 at birth, suggesting that our age zero results were skewed by capture probabilities. Juvenile males are typically the dispersers in mammals (Greenwood 1980), and Hansen et al (2007) found that there was male-biased dispersal of unknownaged cats on Mauna Kea, which could lead to higher juvenile male capture probabilities. Excluding age zero individuals from our model lowered the annual survival estimate, but it was still within the 95% CI for the complete data set.…”
Section: Resultsmentioning
confidence: 99%